Method for increasing the specific surface area of ​​titanium phosphate plate-like particles, and powder made of titanium phosphate-derived plate-like particles

By dispersing titanium phosphate particles in an alkaline solution and drying, the specific surface area is increased, improving slipperiness and refreshing feel in cosmetics without changing particle size, addressing the limitations of existing methods.

JP7620554B2Active Publication Date: 2025-01-23FUJIMI INCORPORATED
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021542006
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-28
Filing Date
2020-05-15
Publication Date
2025-01-23
Estimated Expiration
2040-05-15

AI Technical Summary

Technical Problem

Existing methods for producing titanium phosphate plate-like particles struggle to increase specific surface area without altering particle size, leading to inconsistent physical properties such as slipperiness and refreshing feel when used in cosmetics.

Method used

A method involving dispersing titanium phosphate plate-like particles in an alkaline aqueous solution, followed by neutralization and drying, to form surface irregularities and increase actual specific surface area without changing particle size.

Benefits of technology

The method effectively increases the specific surface area of titanium phosphate particles, enhancing their slipperiness and refreshing feel, making them suitable for use in cosmetics without altering particle size or thickness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620554000006
    Figure 0007620554000006
  • Figure 0007620554000007
    Figure 0007620554000007
  • Figure 0007620554000008
    Figure 0007620554000008
Patent Text Reader

Abstract

The method for increasing the specific surface area of titanium phosphate plate-particles according to the present invention comprises a step for obtaining a liquid in a state where a powder comprising titanium phosphate plate-particles are dispersed in an alkaline aqueous solution.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for increasing the specific surface area of ​​titanium phosphate plate-like particles, and to a powder composed of titanium phosphate-derived plate-like particles. [Background technology]

[0002] Patent Document 1 describes a titanium phosphate powder consisting of plate-like particles (plate-like crystal particles) of titanium phosphate and a method for producing the same. The average thickness of the plate-like particles in this titanium phosphate powder is 0.01 μm or more and less than 0.10 μm, and the aspect ratio, which is the average primary particle diameter of the plate-like particles divided by the average thickness, is 5 or more. Titanium phosphate consisting of such thin plate-like particles has good slip properties between particles, and is therefore suitable as an additive to be added to cosmetics (for example, a white pigment for cosmetics) or a pigment to be added to paints.

[0003] The manufacturing method described in Patent Document 1 can also produce titanium phosphate powder having an average thickness of 0.4 to 0.8 μm and a particle size (average primary particle size) of 3 to 7 μm. In this case, the specific surface area of ​​the plate-like particles constituting the obtained titanium phosphate powder is, for example, 2 to 3 m. 2 / g. The specific surface area of ​​the titanium phosphate plate-like particles obtained by this method varies depending on the particle size and thickness. The specific surface area of ​​the titanium phosphate plate-like particles can be changed, for example, by changing the particle size while maintaining the aspect ratio. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] WO2018 / 180797 Brochure Summary of the Invention [Problem to be solved by the invention]

[0005] However, changing the particle size in order to change the specific surface area of ​​titanium phosphate plate-like particles also changes the physical properties determined by the particle size, such as the slipperiness (mean coefficient of friction (MIU)) of the titanium phosphate plate-like particles, making it difficult to obtain titanium phosphate plate-like particles having both the desired specific surface area and physical properties such as slipperiness. Furthermore, the titanium phosphate powder described in Patent Document 1 leaves room for improvement in terms of the refreshing feeling it provides when used as a powder for cosmetics.

[0006] A first object of the present invention is to provide a method for increasing the specific surface area of ​​titanium phosphate plate-like particles, which can increase the specific surface area without changing the particle size. A second object of the present invention is to provide a powder that provides an excellent refreshing feeling when used as a powder for cosmetics. A third object of the present invention is to provide a powder that satisfies both smoothness and a refreshing feeling when used as a powder for cosmetics. [Means for solving the problem]

[0007] A first aspect of the present invention is a method for increasing the specific surface area of ​​titanium phosphate plate-like particles, which comprises a step of obtaining a liquid in which a powder of titanium phosphate plate-like particles is dispersed in an alkaline aqueous solution.

[0008] A second aspect of the present invention is a powder that satisfies the following configurations (1) and (2). (1) The titanium phosphate-derived plate-like particles are composed of either a titanium phosphate-derived compound in which the hydrogen of titanium phosphate is replaced with an alkali metal, or a titanium phosphate-derived compound in which an alkali metal is contained within the titanium phosphate crystal. (2) The ratio (actual specific surface area / assumed specific surface area) of the actual specific surface area, which is the specific surface area of ​​the titanium phosphate-derived plate-like particles measured by a gas adsorption method, to the assumed specific surface area, which is the specific surface area measured by assuming the outer surface to be flat based on the average particle size and average thickness of the titanium phosphate-derived plate-like particles obtained by microscopic observation, is 1.5 or more.

[0009] A third aspect of the present invention is a powder that satisfies the above configuration (1) and the following configuration (3). (3) The ratio (MMD / MIU) of the mean deviation of the friction coefficient (MMD) to the mean coefficient of friction (MIU) is 0.011 or more. Effect of the Invention

[0010] According to the method of the first aspect of the present invention, the specific surface area of ​​the titanium phosphate plate-like particles can be increased without changing the particle size. According to the second aspect of the present invention, a powder that has an excellent refreshing feeling when used as a powder for cosmetics can be provided. According to the third aspect of the present invention, a powder can be provided that, when used as a powder for cosmetics, exhibits both smoothness and a refreshing feeling. [Brief description of the drawings]

[0011] [Figure 1] 1 shows SEM images of plate-like particles constituting the powders of Samples No. 1-1, No. 4-1, and No. 5-1 obtained in the examples. [Diagram 2] 1 shows SEM images of plate-like particles constituting the powders of Samples No. 1-2, No. 4-2, and No. 5-2 obtained in the examples. [Diagram 3] 1 shows SEM images of plate-like particles constituting the powders of Samples No. 1-3, No. 4-3, and No. 5-3 obtained in the examples. [Figure 4] 1 shows SEM images of plate-like particles constituting the powders of Samples No. 2-1, No. 4-4, and No. 5-4 obtained in the examples. [Diagram 5] 1 shows SEM images of plate-like particles constituting the powders of Samples No. 2-2 and No. 4-5 obtained in the examples. [Figure 6] 1 shows SEM images of plate-like particles constituting the powders of Samples No. 2-3, No. 4-6, and No. 5-5 obtained in the examples. [Figure 7] 1 shows SEM images of plate-like particles constituting the powders of Samples No. 2-4, No. 4-7, and No. 5-6 obtained in the examples. [Figure 8]1 shows SEM images of plate-like particles constituting the powders of Samples No. 2-5 and No. 4-8 obtained in the examples. [Figure 9] 1 shows SEM images of plate-like particles constituting the powders of Samples No. 3-1 and No. 4-9 obtained in the examples. [Figure 10] 1 shows SEM images of plate-like particles constituting the powders of Samples No. 3-2 and No. 4-10 obtained in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] An embodiment of the present invention will be described in detail. Note that the following embodiment shows an example of the present invention, and the present invention is not limited to this embodiment. In addition, various modifications and improvements can be made to the following embodiment, and such modifications and improvements can also be included in the present invention.

[0013] [First embodiment] The method for increasing the specific surface area of ​​titanium phosphate plate-like particles of this embodiment comprises a first step of obtaining a liquid in which a powder of titanium phosphate plate-like particles is dispersed in an alkaline aqueous solution and the liquid has a pH value close to neutral; a second step of separating the particles from the liquid (particle dispersion); and a third step of drying the separated particles. In the first step, a powder of titanium phosphate plate-like particles is dispersed in an alkaline aqueous solution. The method for dispersing the powder can be, for example, the following four methods.

[0014] The first method is to add an alkaline aqueous solution or a compound that becomes alkaline when dissolved in water to a dispersion liquid in which a powder of titanium phosphate plate-like particles is dispersed in water (hereinafter also referred to as a "titanium phosphate dispersion liquid") and mix them. The second method is to place the powder of titanium phosphate plate-like particles in a container and add an alkaline aqueous solution to the container and mix them. The third method is to add a dispersion of titanium phosphate plate-like particles in water or to add titanium phosphate plate-like particles in powder to an alkaline aqueous solution and mix it in. The fourth method is to place a compound that becomes alkaline when dissolved in water in a container, and then add a dispersion of titanium phosphate plate-like particles in water to the container and mix it.

[0015] The powder made of titanium phosphate plate-like particles is a powder made of hexagonal plate-like particles, having an average thickness of 0.01 μm or more and 4 μm or less, an average primary particle diameter of 0.05 μm or more and 20 μm or less, and an aspect ratio, which is the value obtained by dividing the average primary particle diameter by the average thickness, of 5 or more. Examples of the alkaline aqueous solution include an aqueous sodium hydroxide solution, an aqueous potassium hydroxide solution, an aqueous sodium carbonate solution, and an aqueous potassium carbonate solution. Examples of the compound that becomes alkaline when dissolved in water include sodium carbonate and potassium carbonate.

[0016] In the first step, the protons of titanium phosphate are replaced with alkali metal ions, causing a neutralization reaction. As this neutralization reaction progresses, the pH of the alkaline aqueous solution decreases or the pH of the titanium phosphate dispersion increases, and when the neutralization reaction is complete, the pH stabilizes near neutral (for example, between 5 and 9). Continue mixing until this state is reached, or leave to stand after mixing. If leaving to stand after mixing, the time to leave to stand varies depending on the ambient temperature, but about two hours is appropriate at room temperature (25°C).

[0017] In the first step, irregularities are formed on the surface of the titanium phosphate plate-like particles. As a result, the specific surface area of ​​the titanium phosphate plate-like particles increases while the particle size remains unchanged. This specific surface area is not a specific surface area measured assuming the surface of the titanium phosphate plate-like particles to be flat (deemed specific surface area), but a specific surface area measured as a value including the area of ​​the surface formed by the surface irregularities and internal pores (actual specific surface area). The higher the pH of the liquid obtained in the first step, the greater the degree of unevenness formed on the surface of the titanium phosphate plate-like particles. However, if the pH is too high, there is a high possibility that the shape of the titanium phosphate plate-like particles will become distorted. Therefore, it is preferable to set the conditions for the first step so that a stable neutralization reaction occurs at a pH of 5 or more and 9 or less.

[0018] In the second step, for example, centrifugation or suction filtration is carried out to separate the titanium phosphate plate-like particles whose specific surface area has been increased in the first step (strictly speaking, the titanium phosphate-derived plate-like particles) from the water. In the third step, the separated particles are dried until they become a powder. The drying time varies depending on the drying temperature, but at 105°C, about one day is suitable.

[0019] According to the method of the present embodiment, it is possible to increase the specific surface area of ​​hexagonal plate-like titanium phosphate particles having an average thickness of 0.01 μm or more and 4 μm or less, an average primary particle diameter of 0.05 μm or more and 20 μm or less, and an aspect ratio (the value obtained by dividing the average primary particle diameter by the average thickness) of 5 or more, without changing the particle diameter. As a result, the hexagonal plate-like particles constituting the obtained powder have a large specific surface area, but the particle size and thickness do not change, so the aspect ratio is maintained at 5 or more and the average thickness is maintained at 4 μm or less. In other words, both the specific surface area and slipperiness (average coefficient of friction (MIU)) of the titanium phosphate plate-like particles can be adjusted to the desired values.

[0020] In the method of the present embodiment, the particle size and thickness of the titanium phosphate hexagonal plate-like particles do not change due to the treatment performed in the first step, so the assumed surface area (for example, the surface area calculated as the total area of ​​the eight faces constituting the hexagonal prism, assuming the crystal particles to be ideal hexagonal prisms based on the particle size and thickness obtained by image analysis of a micrograph) does not change before and after the first step. However, the actual surface area (the total area of ​​all faces including the unevenness of the surface of the titanium phosphate hexagonal plate-like particles and the faces of the internal holes) increases after the first step. As for the specific surface area, which is the surface area per unit mass, the assumed specific surface area, which is the "assumed surface area / mass", does not change, but the actual specific surface area, which is the "actual surface area / mass", increases.

[0021] The titanium phosphate powder obtained by the method of the present embodiment is suitable as an additive to be added to cosmetics such as sunscreen cosmetics, or as a pigment to be added to paints. The titanium phosphate powder obtained by the method of the present embodiment is also suitable as a white pigment for cosmetics. The titanium phosphate plate-like particles used in the first step of the method of this embodiment can be produced by the method described in Patent Document 1, that is, by reacting raw materials containing titanium and phosphorus by hydrothermal synthesis. The raw materials used in the hydrothermal synthesis can be a mixture of titanium sulfate (IV) (Ti(SO4)2) or titanyl sulfate (TiOSO4) and phosphoric acid (H3PO4). The reaction conditions of the hydrothermal synthesis are described in detail in Patent Document 1.

[0022] [Second embodiment] The powder of this embodiment is a powder made of titanium phosphate-derived plate-like particles composed of either "a titanium phosphate-derived compound in which hydrogen of titanium phosphate is substituted with an alkali metal" or "a titanium phosphate-derived compound in which an alkali metal is contained within titanium phosphate crystals." In addition, the ratio (actual specific surface area / assumed specific surface area) of "actual specific surface area, which is the specific surface area of ​​titanium phosphate-derived plate-like particles measured by gas adsorption method" to "assumed specific surface area, which is the specific surface area measured by assuming the outer surface to be flat from the average particle size and average thickness of titanium phosphate-derived plate-like particles obtained by microscopic observation" is 1.5 or more.

[0023] The titanium phosphate-derived plate-like particles constituting the powder of this embodiment have an average thickness of 0.01 μm or more and 4 μm or less, an average primary particle diameter of 0.05 μm or more and 20 μm or less, and an aspect ratio (the average primary particle diameter divided by the average thickness) of at least 5. The titanium phosphate-derived plate-like particles are hexagonal plate-like particles, and the above-mentioned assumed specific surface area is a value calculated by regarding the hexagonal plate-like particles as ideal hexagonal columns.

[0024] In the powder of this embodiment, the titanium phosphate-derived plate-like particles satisfy the ratio "actual specific surface area / assumed specific surface area ≧1.5", so that the particles have moderate surface irregularities and internal holes, and when used as a powder for cosmetics, it has an excellent refreshing feeling compared to powders consisting of titanium phosphate plate-like particles having an "actual specific surface area / assumed specific surface area<1.5". Therefore, the powder of the present embodiment is suitable as a white pigment for cosmetics. The powder of the present embodiment is also suitable as an additive to be added to cosmetics such as sunscreen cosmetics, or as a pigment to be added to paints.

[0025] The powder of this embodiment can be produced by the following method. This manufacturing method comprises a first step of obtaining a liquid (a dispersion of titanium phosphate-derived plate-like particles) in which a powder of titanium phosphate plate-like particles is dispersed in an alkaline aqueous solution and has a pH value close to neutral; a second step of separating the titanium phosphate-derived plate-like particles from this liquid; and a third step of drying the separated titanium phosphate-derived plate-like particles.

[0026] In the first step, a powder of titanium phosphate plate-like particles is dispersed in an alkaline aqueous solution. The method for dispersing the powder can be, for example, the following four methods. The first method is to add an alkaline aqueous solution or a compound that becomes alkaline when dissolved in water to a dispersion liquid in which a powder of titanium phosphate plate-like particles is dispersed in water (hereinafter also referred to as a "titanium phosphate dispersion liquid") and mix them. The second method is to place the powder of titanium phosphate plate-like particles in a container and add an alkaline aqueous solution to the container and mix them.

[0027] The third method is to add a dispersion of titanium phosphate plate-like particles in water or to add titanium phosphate plate-like particles in powder to an alkaline aqueous solution and mix it in. The fourth method is to place a compound that becomes alkaline when dissolved in water in a container, and then add a dispersion of titanium phosphate plate-like particles in water to the container and mix it.

[0028] The titanium phosphate plate-like particles used are hexagonal plate-like particles having an average thickness of 0.01 μm or more and 4 μm or less, an average primary particle diameter of 0.05 μm or more and 20 μm or less, and an aspect ratio, which is the average primary particle diameter divided by the average thickness, of 5 or more. Examples of the alkaline aqueous solution include an aqueous sodium hydroxide solution, an aqueous potassium hydroxide solution, an aqueous sodium carbonate solution, and an aqueous potassium carbonate solution. Examples of the compound that becomes alkaline when dissolved in water include sodium carbonate and potassium carbonate.

[0029] In the first step, the protons of titanium phosphate are replaced with alkali metal ions, causing a neutralization reaction. As this neutralization reaction progresses, the pH of the alkaline aqueous solution decreases or the pH of the titanium phosphate dispersion increases, and when the neutralization reaction is complete, the pH stabilizes near neutral (for example, between 5 and 9). Continue mixing until this state is reached, or leave to stand after mixing. If leaving to stand after mixing, the time to leave to stand varies depending on the ambient temperature, but about two hours is appropriate at room temperature (25°C).

[0030] In the first step, the titanium phosphate compound is changed into a "titanium phosphate-derived compound in which hydrogen of titanium phosphate is replaced by an alkali metal" or a "titanium phosphate-derived compound in which an alkali metal is contained within the titanium phosphate crystal." Furthermore, in the first step, the formation of irregularities on the surface of the plate-like particles increases the specific surface area of ​​the plate-like particles while the particle size remains unchanged. This specific surface area is not the specific surface area measured assuming the surface of the plate-like particles to be flat (deemed specific surface area), but is the specific surface area measured as a value including the area of ​​the surface formed by the surface irregularities and internal pores (actual specific surface area).

[0031] In the second step, for example, centrifugation or suction filtration is carried out to separate the titanium phosphate-derived plate-like particles (which have a larger specific surface area than the titanium phosphate plate-like particles) from the water in the first step. In the third step, the separated particles are dried until they become a powder. The drying time varies depending on the drying temperature, but at 105°C, about one day is suitable.

[0032] In this manufacturing method, the particle size and thickness of the hexagonal plate-like particles do not change due to the treatment in the first step, so the assumed surface area (for example, the surface area calculated as the total area of ​​the eight faces constituting the hexagonal prism, assuming that the crystal particles are ideal hexagonal prisms based on the particle size and thickness obtained by image analysis of a micrograph) does not change before and after the first step. However, the actual surface area (the total area of ​​all faces including the unevenness of the surface of the hexagonal plate-like particles and the faces of the internal holes) increases after the first step. As for the specific surface area, which is the surface area per unit mass, the assumed specific surface area, which is the "assumed surface area / mass", does not change, but the actual specific surface area, which is the "actual surface area / mass", increases. Therefore, the ratio (actual specific surface area / assumed specific surface area) can be made 1.5 or more.

[0033] The titanium phosphate plate-like particles used in the first step of this manufacturing method can be manufactured by the method described in Patent Document 1, that is, by reacting raw materials containing titanium and phosphorus by hydrothermal synthesis. The raw materials used in the hydrothermal synthesis method can be a mixture of titanium (IV) sulfate (Ti(SO4)2) or titanyl sulfate (TiOSO4) and phosphoric acid (H3PO4). The reaction conditions of the hydrothermal synthesis method are described in detail in Patent Document 1.

[0034] [Third embodiment] The powder of this embodiment is a powder made of titanium phosphate-derived plate-like particles composed of either a "titanium phosphate-derived compound in which hydrogen in titanium phosphate is replaced with an alkali metal" or a "titanium phosphate-derived compound in which an alkali metal is contained within titanium phosphate crystals." The ratio (MMD / MIU) of the mean deviation of the friction coefficient (MMD) to the average friction coefficient (MIU) is 0.011 or more. The titanium phosphate-derived plate-like particles constituting the powder of this embodiment have an average thickness of 0.01 μm or more and 4 μm or less, an average primary particle diameter of 0.05 μm or more and 20 μm or less, and an aspect ratio (the average primary particle diameter divided by the average thickness) of at least 5. The titanium phosphate-derived plate-like particles are hexagonal plate-like particles, and the above-mentioned assumed specific surface area is a value calculated by regarding the hexagonal plate-like particles as ideal hexagonal columns.

[0035] The powder of this embodiment satisfies the "ratio (MMD / MIU) of the mean deviation of the friction coefficient (MMD) to the average coefficient of friction (MIU) of 0.011 or more," and thus achieves both smoothness and a refreshing feel when used as a powder for cosmetics, compared to a powder having a "ratio (MMD / MIU) of the mean deviation of the friction coefficient (MMD) to the average coefficient of friction (MIU) of less than 0.011." For a refreshing feel, MMD is preferably 0.01 or more, and for smoothness, MIU is preferably 1.45 or less.

[0036] Therefore, the powder of the present embodiment is suitable as a white pigment for cosmetics. The powder of the present embodiment is also suitable as an additive to be added to cosmetics such as sunscreen cosmetics, or as a pigment to be added to paints. The powder of this embodiment can be produced by the same method as the powder of the second embodiment described above. EXAMPLES

[0037] The present invention will be described in more detail below with reference to examples. {First embodiment: First aspect of the embodiment} [Production of titanium phosphate powder (Sample No. 1-1) consisting of titanium phosphate hexagonal plate-like particles] First, titanyl sulfate and phosphoric acid were reacted by hydrothermal synthesis to produce titanium phosphate powder. The conditions for hydrothermal synthesis were: titanium concentration [Ti] of the raw material (a mixture of titanyl sulfate and phosphoric acid) was 0.30 mol / L, phosphorus concentration [P] was 3.22 mol / L, the concentration ratio of the two [P] / [Ti] was 11, reaction temperature was 130°C, and reaction time was 5 hours.

[0038] Specifically, first, titanyl sulfate, which is a titanium source, and phosphoric acid, which is a phosphorus source, were mixed to obtain a mixture. Next, the obtained mixture was placed in a reaction vessel (an autoclave with a capacity of 1.4 L) and heated at 130°C for 5 hours. At this time, the reaction vessel was not pressurized, and the pressure inside the vessel was set to a value that was naturally determined by the heating temperature (natural pressurization). After 5 hours, the lid was opened and the slurry in the container was cooled to room temperature, then the slurry was filtered, and the solids remaining on the filter paper were washed with pure water. Next, pure water was added to the washed solids to obtain a slurry, and 29% ammonia water (aqueous solution of ammonium salt) was added to this slurry until the pH became 7. Next, the slurry was filtered, and the same washing as above was performed to separate the solids. The solids were dried (left at a temperature of 105°C for 24 hours) to obtain a powder.

[0039] The powder of sample No. 1-1 obtained in this manner was analyzed using an X-ray diffraction apparatus, and it was confirmed that the particles constituting the powder were crystalline titanium phosphate with the rational formula Ti(HPO4)2·H2O. The whiteness of the powder of Sample No. 1-1 was measured using a UV-2450 ultraviolet-visible spectrophotometer manufactured by Shimadzu Corporation under conditions of illumination D65 and a field of view of 2°, and was found to be 94.6. In other words, the whiteness of the powder of Sample No. 1-1 measured in accordance with JIS Z 8715 was 94.6.

[0040] When the powder of sample No. 1-1 was observed with a scanning electron microscope, it was confirmed that the particles constituting the powder were plate-shaped, and that most of them were hexagonal plate-shaped, as shown in Figure 1(a). In addition, as shown in Figure 1(b), no irregularities were observed on the surfaces of the plate-shaped particles. The average thickness of the crystal particles constituting the powder of sample No. 1-1 was measured from the scanning electron microscope image and found to be 0.44 μm. The average primary particle size of the crystal particles constituting the powder of Sample No. 1-1 was measured to be 3.72 μm by analyzing the images from the scanning electron microscope using the image analysis software "Mac-View ver.4" manufactured by Mountech Co., Ltd. Using these measured values, the aspect ratio of the crystal particles constituting the powder of Sample No. 1-1 was calculated to be 8 (3.72 / 0.44).

[0041] Using these measurements, the specific surface area was calculated assuming that the crystal grains were ideal hexagonal columns, and was found to be 2.22 m 2 / g. In addition, the actual specific surface area of ​​the powder of sample No. 1-1 was measured by the BET flow method (gas adsorption method) using a fully automatic specific surface area measuring device "Macsorb (registered trademark) HM-1210" of Mountec Co., Ltd., and was found to be 2.83 m 2 / g. In addition, the refractive index of the powder of sample No. 1-1 was measured by the following method and was found to be 1.73.

[0042] First, the powder of Sample No. 1-1 and polymethylmethacrylate (film base: transparent resin that serves as the base of the film) were mixed in N-methylpyrrolidone (a solvent capable of dissolving the film base) to disperse the powder and obtain a liquid in which polymethylmethacrylate was dissolved. Multiple versions of this liquid were obtained with different powder contents. Using these liquids, a coating film with a thickness of 600 μm was formed on a PET film, and the film was dried at 80°C to form a film consisting only of powder and resin. After cooling, the film was peeled off from the PET film.

[0043] The refractive index of the films thus obtained was measured using a Metricon Prism Coupler Model 2010 / M refractometer with a 632.8 nm helium-neon laser light source. The measured refractive index of the films was plotted on a graph with the powder content (volume %) on the horizontal axis and the refractive index on the vertical axis, and each plot was approximated by a straight line. The refractive index at the point where the powder content was 100% was determined as the refractive index of the powder.

[0044] Furthermore, the oil absorption per 100 g of the powder of Sample No. 1-1 was measured by a method in accordance with JIS K 5101-13 and was found to be 57 ml / 100 g. In addition, the friction coefficient of the powder of sample No. 1-1, MIU (average friction coefficient), was measured using a friction sensation tester "KES-SE" made by Kato Tech Co., Ltd. During the measurement, double-sided tape was applied to the glass plate of the measurement table, and the powder was placed on top of it and fixed in place. A 10 mm square silicon sensor was placed on the powder and moved under conditions of a static load of 25 g and a scanning speed of 1 mm / sec, and the MIU was measured over a range of 20 mm. The result was that the MIU was 0.98.

[0045] [Implementation of a method for increasing the specific surface area of ​​titanium phosphate plate-like particles (Samples No. 1-2 and No. 1-3)] Next, the powder of Sample No. 1-1 was subjected to the following treatments (treatment with an alkaline aqueous solution, separation, and drying) to carry out the "method for increasing the specific surface area of ​​titanium phosphate plate-like particles" described in the embodiment.

[0046] <Sample No.1-2> 4 g of powder of Sample No. 1-1 was mixed with 36 g of pure water to obtain a dispersion of titanium phosphate platelet particles. 2.60 g of 48% sodium hydroxide solution was added to this dispersion and mixed for 5 minutes, and then left at room temperature (25°C) for two hours. Next, suction filtration was performed to separate the solid content. The separated solid content was dried at 105°C for one day. As a result, powder of Sample No. 1-2 was obtained. The physical properties of the powder of sample No. 1-2 were measured in the same manner as those of the powder of sample No. 1-1.

[0047] The powder of sample No. 1-2 obtained in this way was analyzed using an X-ray diffractometer, and it was found that the particles constituting the powder were crystalline sodium titanium phosphate with the rational formula Na2Ti(PO4)2·H2O. Furthermore, elemental analysis of this powder using an energy dispersive X-ray analyzer (EDX) confirmed the presence of sodium element (Na). In other words, this powder is made up of "titanium phosphate-derived plate-like particles composed of titanium phosphate-derived compounds in which the hydrogen of titanium phosphate has been replaced with an alkali metal." When the powder of sample No. 1-2 was observed with a scanning electron microscope, it was confirmed that the particles constituting the powder were plate-shaped, with many of them being hexagonal plate-shaped, as shown in Figure 2(a).It was also confirmed that the surfaces of the plate-shaped particles were uneven, as shown in Figure 2(b).

[0048] <Sample No.1-3> 4 g of powder of Sample No. 1-1 was mixed with 36 g of pure water to obtain a dispersion of titanium phosphate platelet particles. 3.65 g of 48% potassium hydroxide aqueous solution was added to this dispersion and mixed for 5 minutes, and then left at room temperature (25°C) for two hours. Next, suction filtration was performed to separate the solid content. The separated solid content was dried at 105°C for one day. As a result, powder of Sample No. 1-3 was obtained. The powder of sample No. 1-3 obtained in this way was analyzed using an X-ray diffraction device, and it was found that the particles that make up the powder are almost the same as crystalline titanium phosphate with the rational formula Ti(HPO4)2·H2O. Furthermore, elemental analysis of this powder using an energy dispersive X-ray analyzer (EDX) confirmed the presence of potassium (K). In other words, this powder is made up of "titanium phosphate-derived plate-like particles composed of titanium phosphate-derived compounds with alkali metals contained within the titanium phosphate crystals."

[0049] The physical properties of the powder of sample No. 1-3 were measured in the same manner as those of the powder of sample No. 1-1. When the powder of Sample No. 1-3 was observed with a scanning electron microscope, it was confirmed that the particles constituting the powder were plate-shaped, with many of them being hexagonal plate-shaped, as shown in Figure 3(a).It was also confirmed that the surfaces of the plate-shaped particles were uneven, as shown in Figure 3(b). Table 1 shows the physical property values ​​obtained for Samples No. 1-1 to No. 1-3.

[0050] [Table 1]

[0051] As can be seen from Table 1, the titanium phosphate-derived plate-like particles (No. 1-2, No. 1-3) obtained by treatment with an alkaline aqueous solution have a significantly increased actual specific surface area and a higher pH than the titanium phosphate plate-like particles (No. 1-1) before treatment with an alkaline aqueous solution, but other physical properties remain almost unchanged. In other words, the above-mentioned "method having a treatment step using an alkaline aqueous solution" performed on the powder of sample No. 1-1 makes it possible to increase the specific surface area (actual surface area) without changing the particle size of the titanium phosphate plate-like particles.

[0052] In addition, the whiteness, average thickness, average primary particle size, aspect ratio, refractive index, assumed specific surface area, and MIU of the powders of samples No. 1-2 and No. 1-3 are not significantly different from those of the powder of sample No. 1-1, and have values ​​suitable for use as a powder for cosmetics. Furthermore, while the powder of sample No. 1-1 is acidic, the powders of samples No. 1-2 and No. 1-3 are neutral and have favorable properties (skin-friendly properties) as powders for cosmetics.

[0053] {Second embodiment: First embodiment} [Production of titanium phosphate powder (Sample No. 2-1) consisting of titanium phosphate hexagonal plate-like particles] First, titanyl sulfate and phosphoric acid were reacted by hydrothermal synthesis to produce titanium phosphate powder. The conditions for hydrothermal synthesis were: titanium concentration [Ti] of the raw material (a mixture of titanyl sulfate and phosphoric acid) was 0.30 mol / L, phosphorus concentration [P] was 3.22 mol / L, the concentration ratio of the two [P] / [Ti] was 11, reaction temperature was 130°C, and reaction time was 3 hours. Specifically, first, titanyl sulfate, which is a titanium source, and phosphoric acid, which is a phosphorus source, were mixed to obtain a mixture. Next, the obtained mixture was placed in a reaction vessel (an autoclave with a capacity of 200 L) and heated at 130°C for 3 hours. At this time, the reaction vessel was not pressurized, and the pressure inside the vessel was set to a value that was naturally determined by the heating temperature (natural pressurization).

[0054] After 3 hours, the lid was opened and the slurry in the container was cooled to room temperature, then the slurry was filtered, and the solids remaining on the filter paper were washed with pure water. Next, pure water was added to the washed solids to obtain a slurry, and 29% ammonia water (aqueous solution of ammonium salt) was added to this slurry until the pH became 7. Next, the slurry was filtered, and the same washing as above was performed to separate the solids. The solids were dried (left at a temperature of 105°C for 24 hours) to obtain a powder.

[0055] The powder of sample No. 2-1 obtained in this manner was analyzed using an X-ray diffraction apparatus, and it was confirmed that the particles constituting the powder were crystalline titanium phosphate with the rational formula Ti(HPO4)2·H2O. The physical properties of the powder sample No. 2-1 were measured in the same manner as those of the powder sample No. 1-1. When the powder of sample No. 2-1 was observed with a scanning electron microscope, it was confirmed that the particles constituting the powder were plate-shaped, with many of them being hexagonal plate-shaped, as shown in Figure 4(a).In addition, as shown in Figure 4(b), no irregularities were observed on the surfaces of the plate-shaped particles.

[0056] [Implementation of a method for increasing the specific surface area of ​​titanium phosphate platelet particles (Samples No. 2-2, No. 2-3, No. 2-4, No. 2-5)] Next, the powder of Sample No. 2-1 was subjected to the following treatments (treatment with an alkaline aqueous solution, separation, and drying) to carry out the "method for increasing the specific surface area of ​​titanium phosphate plate-like particles" described in the embodiment.

[0057] <Sample No.2-2> 4 g of powder of sample No. 2-1 was mixed with 36 g of pure water to obtain a dispersion of titanium phosphate platelet particles. 2.60 g of 48% sodium hydroxide solution was added to this dispersion and mixed for 5 minutes, and then left at room temperature (25°C) for two hours. Next, suction filtration was performed to separate the solid content. The separated solid content was dried at 105°C for one day. This resulted in the powder of sample No. 2-2.

[0058] The powder of sample No. 2-2 obtained in this way was analyzed using an X-ray diffraction apparatus, and it was found that the particles constituting the powder were crystalline sodium titanium phosphate with the rational formula Na2Ti(PO4)2·H2O. Furthermore, elemental analysis of this powder using an energy dispersive X-ray analyzer (EDX) confirmed the presence of sodium element (Na). In other words, this powder is made up of "plate-like particles derived from titanium phosphate, which are composed of titanium phosphate-derived compounds in which the hydrogen of titanium phosphate has been replaced with an alkali metal."

[0059] The physical properties of the powder of sample No. 2-2 were measured in the same manner as those of the powder of sample No. 1-1. When the powder of sample No. 2-2 was observed with a scanning electron microscope, it was confirmed that the particles constituting the powder were plate-shaped, with many of them being hexagonal plate-shaped, as shown in Figure 5(a).It was also confirmed that the surfaces of the plate-shaped particles were uneven, as shown in Figure 5(b).

[0060] <Sample No.2-3> 4 g of powder of sample No. 2-1 was mixed with 36 g of pure water to obtain a dispersion of titanium phosphate platelet particles. 3.65 g of 48% potassium hydroxide aqueous solution was added to this dispersion and mixed for 5 minutes, and then left at room temperature (25°C) for two hours. Next, suction filtration was performed to separate the solid content. The separated solid content was dried at 105°C for one day. As a result, powder of sample No. 2-3 was obtained.

[0061] The powder of sample No. 2-3 obtained in this way was analyzed using an X-ray diffraction device, and it was found that the particles that make up the powder are almost the same as crystalline titanium phosphate with the rational formula Ti(HPO4)2·H2O. Furthermore, elemental analysis of this powder using an energy dispersive X-ray analyzer (EDX) confirmed the presence of potassium (K). In other words, this powder is made up of "titanium phosphate-derived plate-like particles composed of titanium phosphate-derived compounds with alkali metals contained within the titanium phosphate crystals."

[0062] The physical properties of the powder of sample No. 2-3 were measured in the same manner as those of the powder of sample No. 1-1. When the powder of sample No. 2-3 was observed with a scanning electron microscope, it was confirmed that the particles constituting the powder were plate-shaped, with many of them being hexagonal plate-shaped, as shown in Figure 6(a).It was also confirmed that the surfaces of the plate-shaped particles were uneven, as shown in Figure 6(b).

[0063] <Sample No.2-4> 4 g of powder of sample No. 2-1 was mixed with 36 g of pure water to obtain a dispersion of titanium phosphate platelet particles. 1.65 g of sodium carbonate powder was added to this dispersion and mixed for 5 minutes, and then left at room temperature (25°C) for two hours. Next, suction filtration was performed to separate the solid content. The separated solid content was dried at 105°C for one day. As a result, powder of sample No. 2-4 was obtained.

[0064] The powder of sample No. 2-4 obtained in this way was analyzed using an X-ray diffraction apparatus, and it was found that the particles constituting the powder were crystalline sodium titanium phosphate with the rational formula Na2Ti(PO4)2·H2O. Furthermore, elemental analysis of this powder using an energy dispersive X-ray analyzer (EDX) confirmed the presence of sodium element (Na). In other words, this powder is made up of "plate-like particles derived from titanium phosphate, which are composed of titanium phosphate-derived compounds in which the hydrogen of titanium phosphate has been replaced with an alkali metal."

[0065] The physical properties of the powder of sample No. 2-4 were measured in the same manner as those of the powder of sample No. 1-1. When the powder of sample No. 2-4 was observed with a scanning electron microscope, it was confirmed that the particles constituting the powder were plate-shaped, with many of them being hexagonal plate-shaped, as shown in Figure 7(a).It was also confirmed that the surfaces of the plate-shaped particles were uneven, as shown in Figure 7(b).

[0066] <Sample No.2-5> 4 g of powder of sample No. 2-1 was mixed with 36 g of pure water to obtain a dispersion of titanium phosphate platelet particles. 2.16 g of potassium carbonate powder was added to this dispersion and mixed for 5 minutes, and then left at room temperature (25°C) for two hours. Next, suction filtration was performed to separate the solid content. The separated solid content was dried at 105°C for one day. As a result, powder of sample No. 2-5 was obtained.

[0067] The powder of sample No. 2-5 obtained in this way was analyzed using an X-ray diffraction apparatus, and it was found that the particles that make up the powder are almost the same as crystalline titanium phosphate with the rational formula Ti(HPO4)2·H2O. Furthermore, elemental analysis of this powder using an energy dispersive X-ray analyzer (EDX) confirmed the presence of potassium (K). In other words, this powder is made up of "titanium phosphate-derived plate-like particles composed of titanium phosphate-derived compounds with alkali metals contained within the titanium phosphate crystals."

[0068] The physical properties of the powder of sample No. 2-5 were measured in the same manner as those of the powder of sample No. 1-1. When the powder of sample No. 2-5 was observed with a scanning electron microscope, it was confirmed that the particles constituting the powder were plate-shaped, with many of them being hexagonal plate-shaped, as shown in Figure 8(a).It was also confirmed that the surfaces of the plate-shaped particles were uneven, as shown in Figure 8(b). These values ​​are shown in Table 2. Although the refractive indexes of the powders of Samples No. 2-1 to No. 2-5 were not measured, they can be assumed to be approximately the same as the refractive indexes of the powders of Samples No. 1-1 to No. 1-3.

[0069] [Table 2]

[0070] As can be seen from Table 2, the titanium phosphate platelet particles (No. 2-2 to No. 2-5) after treatment with an alkaline aqueous solution have a significantly increased actual specific surface area and a higher pH than the titanium phosphate platelet particles (No. 2-1) before treatment, but other physical properties remain almost unchanged. In other words, the above-mentioned "method having a treatment step using an alkaline aqueous solution" performed on the powder of sample No. 2-1 makes it possible to increase the specific surface area (actual surface area) without changing the particle size of the titanium phosphate plate-like particles.

[0071] In addition, the whiteness, average thickness, average primary particle size, aspect ratio, assumed specific surface area, and MIU of the powders of samples No. 2-2 to No. 2-5 are not significantly different from those of sample No. 2-1, and have values ​​suitable for use as powders for cosmetics. Furthermore, while the powder of sample No. 2-1 is acidic, the powders of samples No. 2-2 to No. 2-5 are neutral and have favorable properties (skin-friendly properties) as powders for cosmetics.

[0072] {Third embodiment: First embodiment} [Production of titanium phosphate powder (Sample No. 3-1) consisting of titanium phosphate hexagonal plate-like particles] First, titanyl sulfate and phosphoric acid were reacted by hydrothermal synthesis to produce titanium phosphate powder. The conditions for hydrothermal synthesis were: titanium concentration [Ti] of the raw material (a mixture of titanyl sulfate and phosphoric acid) was 0.30 mol / L, phosphorus concentration [P] was 3.93 mol / L, the concentration ratio of the two [P] / [Ti] was 13, reaction temperature was 90°C, and reaction time was 5 hours. Specifically, first, titanyl sulfate, which is a titanium source, and phosphoric acid, which is a phosphorus source, were mixed to obtain a mixture. Next, the obtained mixture was placed in a reaction vessel (an autoclave with a capacity of 1.4 L) and heated at 90°C for 5 hours. At this time, the reaction vessel was not pressurized, and the pressure inside the vessel was set to a value that was naturally determined by the heating temperature (natural pressurization).

[0073] After 5 hours, the lid was opened and the slurry in the container was cooled to room temperature, then the slurry was filtered, and the solids remaining on the filter paper were washed with pure water. Next, pure water was added to the washed solids to obtain a slurry, and 29% ammonia water (aqueous solution of ammonium salt) was added to this slurry until the pH became 7. Next, the slurry was filtered, and the same washing as above was performed to separate the solids. The solids were dried (left at a temperature of 105°C for 24 hours) to obtain a powder.

[0074] The powder of sample No. 3-1 obtained in this manner was analyzed using an X-ray diffraction apparatus, and it was confirmed that the particles constituting the powder were crystalline titanium phosphate with the rational formula Ti(HPO4)2·H2O. The physical properties of the powder sample No. 3-1 were measured in the same manner as those of the powder sample No. 1-1. When the powder of sample No. 3-1 was observed with a scanning electron microscope, it was confirmed that the particles constituting the powder were plate-like, with many of them being hexagonal plate-like, as shown in Figure 9. Furthermore, no irregularities were observed on the surfaces of the plate-like particles.

[0075] [Implementation of a method for increasing the specific surface area of ​​titanium phosphate platelet particles (Sample No. 3-2)] Next, the powder of Sample No. 3-1 was subjected to the following treatments (treatment with an alkaline aqueous solution, separation, and drying) to carry out the "method for increasing the specific surface area of ​​titanium phosphate plate-like particles" described in the embodiment.

[0076] <Sample No.3-2> 4 g of powder of Sample No. 3-1 was mixed with 36 g of pure water to obtain a dispersion of titanium phosphate platelet particles. 2.60 g of 48% sodium hydroxide solution was added to this dispersion and mixed for 5 minutes, and then left at room temperature (25°C) for two hours. Next, suction filtration was performed to separate the solid content. The separated solid content was dried at 105°C for one day. As a result, powder of Sample No. 3-2 was obtained.

[0077] The powder of sample No. 3-2 obtained in this way was analyzed using an X-ray diffraction device, and it was found that the particles constituting the powder were crystalline sodium titanium phosphate with the rational formula Na2Ti(PO4)2·H2O. Furthermore, elemental analysis of this powder using an energy dispersive X-ray analyzer (EDX) confirmed the presence of sodium element (Na). In other words, this powder is made up of "titanium phosphate-derived plate-like particles composed of titanium phosphate-derived compounds in which the hydrogen of titanium phosphate has been replaced with an alkali metal."

[0078] The physical properties of the powder of sample No. 3-2 were measured in the same manner as those of the powder of sample No. 1-1. When the powder of sample No. 3-2 was observed with a scanning electron microscope, it was confirmed that the particles constituting the powder were plate-shaped, with many of them being hexagonal plate-shaped, as shown in Figure 10. It was also confirmed that the surfaces of the plate-shaped particles were uneven. These values ​​are shown in Table 3. Although the refractive indexes of the powders of Samples No. 3-1 and No. 3-2 were not measured, they can be assumed to be approximately the same as the refractive indexes of the powders of Samples No. 1-1 to No. 1-3.

[0079] [Table 3]

[0080] As can be seen from Table 3, the titanium phosphate platelet particles (No. 3-2) after treatment with an alkaline aqueous solution have a significantly increased actual specific surface area and a higher pH than the titanium phosphate platelet particles (No. 3-1) before treatment, but other physical properties remain almost unchanged. In other words, the above-mentioned "method having a treatment step using an alkaline aqueous solution" performed on the powder of sample No. 3-1 makes it possible to increase the specific surface area (actual surface area) without changing the particle size of the titanium phosphate plate-like particles.

[0081] In addition, the whiteness, average thickness, average primary particle size, aspect ratio, and assumed specific surface area of ​​the powder of sample No. 3-2 are not significantly different from those of the powder of sample No. 3-1, and the values ​​are suitable for use as a powder for cosmetics. Furthermore, while the powder of sample No. 3-1 is acidic, the powder of sample No. 3-2 is neutral and has favorable properties (skin-friendly properties) as a powder for cosmetics.

[0082] {Fourth embodiment: Second embodiment} <Sample No.4-1> First, titanyl sulfate and phosphoric acid were reacted by hydrothermal synthesis to produce titanium phosphate powder. The conditions for hydrothermal synthesis were: titanium concentration [Ti] of the raw material (a mixture of titanyl sulfate and phosphoric acid) was 0.30 mol / L, phosphorus concentration [P] was 3.22 mol / L, the concentration ratio of the two [P] / [Ti] was 11, reaction temperature was 130°C, and reaction time was 5 hours. Specifically, first, titanyl sulfate, which is a titanium source, and phosphoric acid, which is a phosphorus source, were mixed to obtain a mixture. Next, the obtained mixture was placed in a reaction vessel (an autoclave with a capacity of 1.4 L) and heated at 130°C for 5 hours. At this time, the reaction vessel was not pressurized, and the pressure inside the vessel was set to a value that was naturally determined by the heating temperature (natural pressurization).

[0083] After 5 hours, the lid was opened and the slurry in the container was cooled to room temperature, then the slurry was filtered, and the solids remaining on the filter paper were washed with pure water. Next, pure water was added to the washed solids to obtain a slurry, and 29% ammonia water (aqueous solution of ammonium salt) was added to this slurry until the pH became 7. Next, the slurry was filtered, and the same washing as above was performed to separate the solids. The solids were dried (left at a temperature of 105°C for 24 hours) to obtain a powder.

[0084] The powder of sample No. 4-1 obtained in this manner was analyzed using an X-ray diffraction apparatus, and it was confirmed that the particles constituting the powder were crystalline titanium phosphate with the rational formula Ti(HPO4)2·H2O. In other words, this powder is neither a powder consisting of "titanium phosphate-derived plate-like particles composed of a titanium phosphate-derived compound in which the hydrogen of titanium phosphate has been replaced with an alkali metal" nor a powder consisting of "titanium phosphate-derived plate-like particles composed of a titanium phosphate-derived compound in which an alkali metal is contained within the titanium phosphate crystals."

[0085] The whiteness of the powder of Sample No. 4-1 was measured using a UV-2450 ultraviolet-visible spectrophotometer manufactured by Shimadzu Corporation under conditions of illumination D65 and a field of view of 2°, and was found to be 94.6. In other words, the whiteness of the powder of Sample No. 4-1 measured in accordance with JIS Z 8715 was 94.6. When the powder of sample No. 4-1 was observed with a scanning electron microscope, it was confirmed that the particles constituting the powder were plate-shaped, with many of them being hexagonal plate-shaped, as shown in Figure 1(a). In addition, as shown in Figure 1(b), no irregularities were observed on the surfaces of the plate-shaped particles. The average thickness of the crystal particles constituting the powder of sample No. 4-1 was measured from the scanning electron microscope image and found to be 0.44 μm.

[0086] The average primary particle size of the crystal particles constituting the powder of Sample No. 4-1 was measured to be 3.72 μm by analyzing the images from the scanning electron microscope using the image analysis software "Mac-View ver.4" made by Mountech Co., Ltd. Using these measured values, the aspect ratio of the crystal particles constituting the powder of Sample No. 4-1 was calculated to be 8 (3.72 / 0.44).

[0087] Using these measurements, the specific surface area was calculated assuming that the crystal grains were ideal hexagonal columns, and was found to be 2.22 m 2 The actual specific surface area of ​​the powder of Sample No. 4-1 was measured by the BET flow method (gas adsorption method) using a fully automatic specific surface area measuring device "Macsorb (registered trademark) HM-1210" manufactured by Mountech Co., Ltd., and was found to be 2.83 m 2 As a result, the value of "actual specific surface area / presumed specific surface area" was 1.27. In addition, the refractive index of the powder of sample No. 4-1 was measured by the following method and was found to be 1.73.

[0088] First, the powder of Sample No. 4-1 and polymethylmethacrylate (film base: transparent resin that serves as the base of the film) were mixed in N-methylpyrrolidone (a solvent capable of dissolving the film base) to disperse the powder and obtain a liquid in which polymethylmethacrylate was dissolved. Multiple versions of this liquid were obtained with different powder contents. Using these liquids, a coating film with a thickness of 600 μm was formed on a PET film, and the film was dried at 80°C to form a film consisting only of powder and resin. After cooling, the film was peeled off from the PET film.

[0089] The refractive index of the films thus obtained was measured using a Metricon Prism Coupler Model 2010 / M refractometer with a 632.8 nm helium-neon laser light source. The measured refractive index of the films was plotted on a graph with the powder content (volume %) on the horizontal axis and the refractive index on the vertical axis, and each plot was approximated by a straight line. The refractive index at the point where the powder content was 100% was determined as the refractive index of the powder.

[0090] Furthermore, the oil absorption per 100 g of the powder of Sample No. 4-1 was measured by a method in accordance with JIS K 5101-13 and was found to be 57 ml / 100 g. In addition, the friction coefficient of the powder of sample No. 4-1, MIU (average friction coefficient), was measured using a friction sensation tester "KES-SE" made by Kato Tech Co., Ltd. During the measurement, double-sided tape was applied to the glass plate of the measurement table, and the powder was placed on top of it and fixed in place. A 10 mm square silicon sensor was placed on the powder and moved under conditions of a static load of 25 g and a scanning speed of 1 mm / sec, and the MIU was measured over a range of 20 mm. The MIU was 0.98.

[0091] <Sample No.4-2> 4 g of powder of sample No. 4-1 was mixed with 36 g of pure water to obtain a dispersion of titanium phosphate platelet particles. 2.60 g of 48% sodium hydroxide solution was added to this dispersion and mixed for 5 minutes, and then left at room temperature (25°C) for two hours. Next, suction filtration was performed to separate the solid content. The separated solid content was dried at 105°C for one day. As a result, powder of sample No. 4-2 was obtained.

[0092] The powder of sample No. 4-2 obtained in this way was analyzed using an X-ray diffraction device, and it was found that the particles constituting the powder were crystalline sodium titanium phosphate with the rational formula Na2Ti(PO4)2·H2O. Furthermore, elemental analysis of this powder using an energy dispersive X-ray analyzer (EDX) confirmed the presence of sodium element (Na). In other words, this powder is made up of "titanium phosphate-derived plate-like particles composed of titanium phosphate-derived compounds in which the hydrogen of titanium phosphate has been replaced with an alkali metal."

[0093] The physical properties of the powder of sample No. 4-2 were measured in the same manner as the powder of sample No. 4-1. The physical properties were as shown in Table 4. As shown in Table 4, the value of "actual specific surface area / presumed specific surface area" was 6.68. When the powder of sample No. 4-2 was observed with a scanning electron microscope, it was confirmed that the particles constituting the powder were plate-shaped, with many of them being hexagonal plate-shaped, as shown in Figure 2(a).It was also confirmed that the surfaces of the plate-shaped particles were uneven, as shown in Figure 2(b).

[0094] <Sample No.4-3> 4 g of powder of sample No. 4-1 was mixed with 36 g of pure water to obtain a dispersion of titanium phosphate platelet particles. 3.65 g of 48% potassium hydroxide aqueous solution was added to this dispersion and mixed for 5 minutes, and then left at room temperature (25°C) for two hours. Next, suction filtration was performed to separate the solid content. The separated solid content was dried at 105°C for one day. As a result, powder of sample No. 4-3 was obtained.

[0095] The powder of sample No. 4-3 obtained in this way was analyzed using an X-ray diffraction device, and it was found that the particles that make up the powder are almost the same as crystalline titanium phosphate with the rational formula Ti(HPO4)2·H2O. Furthermore, elemental analysis of this powder using an energy dispersive X-ray analyzer (EDX) confirmed the presence of potassium (K). In other words, this powder is made up of "titanium phosphate-derived plate-like particles composed of titanium phosphate-derived compounds with alkali metals contained within the titanium phosphate crystals."

[0096] The physical properties of the powder of sample No. 4-3 were measured in the same manner as those of the powder of sample No. 4-1. The physical properties were as shown in Table 4. As shown in Table 4, the value of "actual specific surface area / assumed specific surface area" was 24.6. When the powder of sample No. 4-3 was observed with a scanning electron microscope, it was confirmed that the particles constituting the powder were plate-shaped, with many of them being hexagonal plate-shaped, as shown in Figure 3(a).It was also confirmed that the surfaces of the plate-shaped particles were uneven, as shown in Figure 3(b).

[0097] <Sample No.4-4> First, titanyl sulfate and phosphoric acid were reacted by hydrothermal synthesis to produce titanium phosphate powder. The conditions for hydrothermal synthesis were: titanium concentration [Ti] of the raw material (a mixture of titanyl sulfate and phosphoric acid) was 0.30 mol / L, phosphorus concentration [P] was 3.22 mol / L, the concentration ratio of the two [P] / [Ti] was 11, reaction temperature was 130°C, and reaction time was 3 hours. Specifically, first, titanyl sulfate, which is a titanium source, and phosphoric acid, which is a phosphorus source, were mixed to obtain a mixture. Next, the obtained mixture was placed in a reaction vessel (an autoclave with a capacity of 200 L) and heated at 130°C for 3 hours. At this time, the reaction vessel was not pressurized, and the pressure inside the vessel was set to a value that was naturally determined by the heating temperature (natural pressurization).

[0098] After 3 hours, the lid was opened and the slurry in the container was cooled to room temperature, then the slurry was filtered, and the solids remaining on the filter paper were washed with pure water. Next, pure water was added to the washed solids to obtain a slurry, and 29% ammonia water (aqueous solution of ammonium salt) was added to this slurry until the pH became 7. Next, the slurry was filtered, and the same washing as above was performed to separate the solids. The solids were dried (left at a temperature of 105°C for 24 hours) to obtain a powder.

[0099] The powder of sample No. 4-4 obtained in this manner was analyzed using an X-ray diffraction apparatus, and it was confirmed that the particles constituting the powder were crystalline titanium phosphate with the rational formula Ti(HPO4)2·H2O. In other words, this powder is neither a powder consisting of "titanium phosphate-derived plate-like particles composed of a titanium phosphate-derived compound in which the hydrogen of titanium phosphate has been replaced with an alkali metal" nor a powder consisting of "titanium phosphate-derived plate-like particles composed of a titanium phosphate-derived compound in which an alkali metal is contained within the titanium phosphate crystals."

[0100] The physical properties of the powder of sample No. 4-4 were measured in the same manner as the powder of sample No. 4-1. The physical properties were as shown in Table 4. As shown in Table 4, the value of "actual specific surface area / presumed specific surface area" was 1.33. When the powder of sample No. 4-4 was observed with a scanning electron microscope, it was confirmed that the particles constituting the powder were plate-shaped, with many of them being hexagonal plate-shaped, as shown in Figure 4(a).In addition, as shown in Figure 4(b), no irregularities were observed on the surfaces of the plate-shaped particles.

[0101] <Sample No.4-5> 4g of the powder of sample No. 4-4 was mixed with 36g of pure water to obtain a dispersion of titanium phosphate plate-like particles. 2.60g of 48% sodium hydroxide solution was added to this dispersion and mixed for 5 minutes, then left at room temperature (25°C) for 2 hours. Next, suction filtration was performed to separate the solid content. The separated solid content was dried at 105°C for 1 day. As a result, powder of sample No. 4-5 was obtained.

[0102] The powder of sample No. 4-5 obtained in this way was analyzed using an X-ray diffraction apparatus, and it was found that the particles constituting the powder were crystalline sodium titanium phosphate with the rational formula Na2Ti(PO4)2·H2O. Furthermore, elemental analysis of this powder using an energy dispersive X-ray analyzer (EDX) confirmed the presence of sodium (Na). In other words, this powder is made up of "plate-like particles derived from titanium phosphate, which are composed of titanium phosphate-derived compounds in which the hydrogen of titanium phosphate has been replaced with an alkali metal."

[0103] The physical properties of the powder of sample No. 4-5 were measured in the same manner as the powder of sample No. 4-1. The physical properties were as shown in Table 4. As shown in Table 4, the value of "actual specific surface area / presumed specific surface area" was 8.28. When the powder of sample No. 4-5 was observed with a scanning electron microscope, it was confirmed that the particles constituting the powder were plate-shaped, with many of them being hexagonal plate-shaped, as shown in Figure 5(a).It was also confirmed that the surfaces of the plate-shaped particles were uneven, as shown in Figure 5(b).

[0104] <Sample No.4-6> 4g of the powder of sample No. 4-4 was mixed with 36g of pure water to obtain a dispersion of titanium phosphate platelet particles. 3.65g of 48% potassium hydroxide aqueous solution was added to this dispersion and mixed for 5 minutes, and then left at room temperature (25°C) for two hours. Next, suction filtration was performed to separate the solid content. The separated solid content was dried at 105°C for one day. This resulted in the powder of sample No. 4-6.

[0105] The powder of sample No. 4-6 obtained in this way was analyzed using an X-ray diffraction device, and it was found that the particles that make up the powder are almost the same as crystalline titanium phosphate with the rational formula Ti(HPO4)2·H2O. Furthermore, elemental analysis of this powder using an energy dispersive X-ray analyzer (EDX) confirmed the presence of potassium (K). In other words, this powder is made up of "titanium phosphate-derived plate-like particles composed of titanium phosphate-derived compounds with alkali metals inside the titanium phosphate crystals."

[0106] The physical properties of the powder of sample No. 4-6 were measured in the same manner as the powder of sample No. 4-1. The physical properties were as shown in Table 4. As shown in Table 4, the value of "actual specific surface area / assumed specific surface area" was 19.7. When the powder of Sample No. 4-6 was observed with a scanning electron microscope, it was confirmed that the particles constituting the powder were plate-shaped, with many of them being hexagonal plate-shaped, as shown in Figure 6(a).It was also confirmed that the surfaces of the plate-shaped particles were uneven, as shown in Figure 6(b).

[0107] <Sample No.4-7> 4g of the powder of sample No. 4-4 was mixed with 36g of pure water to obtain a dispersion of titanium phosphate platelet particles. 1.65g of sodium carbonate powder was added to this dispersion and mixed for 5 minutes, and then left at room temperature (25°C) for two hours. Next, suction filtration was performed to separate the solid content. The separated solid content was dried at 105°C for one day. This resulted in the powder of sample No. 4-7.

[0108] The powder of sample No. 4-7 obtained in this way was analyzed using an X-ray diffraction apparatus, and it was found that the particles constituting the powder were crystalline sodium titanium phosphate with the rational formula Na2Ti(PO4)2·H2O. Furthermore, elemental analysis of this powder using an energy dispersive X-ray analyzer (EDX) confirmed the presence of sodium (Na). In other words, this powder is made up of "plate-like particles derived from titanium phosphate, which are composed of titanium phosphate-derived compounds in which the hydrogen of titanium phosphate has been replaced with an alkali metal."

[0109] The physical properties of the powder of sample No. 4-7 were measured in the same manner as the powder of sample No. 4-1. The physical properties were as shown in Table 4. As shown in Table 4, the value of "actual specific surface area / presumed specific surface area" was 2.63. When the powder of sample No. 4-7 was observed with a scanning electron microscope, it was confirmed that the particles constituting the powder were plate-shaped, with many of them being hexagonal plate-shaped, as shown in Figure 7(a).It was also confirmed that the surfaces of the plate-shaped particles were uneven, as shown in Figure 7(b).

[0110] <Sample No.4-8> 4g of the powder of sample No. 4-4 was mixed with 36g of pure water to obtain a dispersion of titanium phosphate platelet particles. 2.16g of potassium carbonate powder was added to this dispersion and mixed for 5 minutes, and then left at room temperature (25°C) for two hours. Next, suction filtration was performed to separate the solid content. The separated solid content was dried at 105°C for one day. As a result, powder of sample No. 4-8 was obtained.

[0111] The powder of sample No. 4-8 obtained in this way was analyzed using an X-ray diffraction apparatus, and it was found that the particles that make up the powder are almost the same as crystalline titanium phosphate with the rational formula Ti(HPO4)2·H2O. Furthermore, elemental analysis of this powder using an energy dispersive X-ray analyzer (EDX) confirmed the presence of potassium (K). In other words, this powder is made up of "titanium phosphate-derived plate-like particles composed of titanium phosphate-derived compounds with alkali metals contained within the titanium phosphate crystals."

[0112] The physical properties of the powder of sample No. 4-8 were measured in the same manner as the powder of sample No. 4-1. The physical properties were as shown in Table 4. As shown in Table 4, the value of "actual specific surface area / presumed specific surface area" was 3.64. When the powder of sample No. 4-8 was observed with a scanning electron microscope, it was confirmed that the particles constituting the powder were plate-shaped, with many of them being hexagonal plate-shaped, as shown in Figure 8(a).It was also confirmed that the surfaces of the plate-shaped particles were uneven, as shown in Figure 8(b).

[0113] <Sample No.4-9> First, titanyl sulfate and phosphoric acid were reacted by hydrothermal synthesis to produce titanium phosphate powder. The conditions for hydrothermal synthesis were: titanium concentration [Ti] of the raw material (a mixture of titanyl sulfate and phosphoric acid) was 0.30 mol / L, phosphorus concentration [P] was 3.93 mol / L, the concentration ratio of the two [P] / [Ti] was 13, reaction temperature was 90°C, and reaction time was 5 hours. Specifically, first, titanyl sulfate, which is a titanium source, and phosphoric acid, which is a phosphorus source, were mixed to obtain a mixture. Next, the obtained mixture was placed in a reaction vessel (an autoclave with a capacity of 1.4 L) and heated at 90°C for 5 hours. At this time, the reaction vessel was not pressurized, and the pressure inside the vessel was set to a value that was naturally determined by the heating temperature (natural pressurization).

[0114] After 5 hours, the lid was opened and the slurry in the container was cooled to room temperature, then the slurry was filtered, and the solids remaining on the filter paper were washed with pure water. Next, pure water was added to the washed solids to obtain a slurry, and 29% ammonia water (aqueous solution of ammonium salt) was added to this slurry until the pH became 7. Next, the slurry was filtered, and the same washing as above was performed to separate the solids. The solids were dried (left at a temperature of 105°C for 24 hours) to obtain a powder.

[0115] The powder of sample No. 4-9 obtained in this manner was analyzed using an X-ray diffraction apparatus, and it was confirmed that the particles constituting the powder were crystalline titanium phosphate with the rational formula Ti(HPO4)2·H2O. In other words, this powder is neither a powder consisting of "titanium phosphate-derived plate-like particles composed of a titanium phosphate-derived compound in which the hydrogen of titanium phosphate has been replaced with an alkali metal" nor a powder consisting of "titanium phosphate-derived plate-like particles composed of a titanium phosphate-derived compound in which an alkali metal is contained within the titanium phosphate crystals."

[0116] The physical properties of the powder of sample No. 4-9 were measured in the same manner as those of the powder of sample No. 4-1. The values ​​of each physical property were as shown in Table 4. As shown in Table 4, the value of "actual specific surface area / presumed specific surface area" was 0.93. When the powder of Sample No. 4-9 was observed with a scanning electron microscope, it was confirmed that the particles constituting the powder were plate-like, with many of them being hexagonal plate-like, as shown in Figure 9. Furthermore, no irregularities were observed on the surfaces of the plate-like particles.

[0117] <Sample No.4-10> 4 g of the powder of sample No. 4-9 was mixed with 36 g of pure water to obtain a dispersion of titanium phosphate platelet particles. 2.60 g of 48% sodium hydroxide solution was added to this dispersion and mixed for 5 minutes, and then the mixture was left at room temperature (25°C) for two hours. Next, the solid content was separated by suction filtration. The separated solid content was dried at 105°C for one day. As a result, powder of sample No. 4-10 was obtained.

[0118] The powder of sample No. 4-10 obtained in this way was analyzed using an X-ray diffraction apparatus, and it was found that the particles constituting the powder were crystalline sodium titanium phosphate with the rational formula Na2Ti(PO4)2·H2O. Furthermore, elemental analysis of this powder using an energy dispersive X-ray analyzer (EDX) confirmed the presence of sodium element (Na). In other words, this powder is made up of "plate-like particles derived from titanium phosphate, which are composed of titanium phosphate-derived compounds in which the hydrogen of titanium phosphate has been replaced with an alkali metal."

[0119] The physical properties of the powder of sample No. 4-10 were measured in the same manner as the powder of sample No. 4-1. The physical properties were as shown in Table 4. As shown in Table 4, the value of "actual specific surface area / presumed specific surface area" was 1.57. When the powder of sample No. 4-10 was observed with a scanning electron microscope, it was confirmed that the particles constituting the powder were plate-shaped, with many of them being hexagonal plate-shaped, as shown in Figure 10. It was also confirmed that the surfaces of the plate-shaped particles were uneven. The physical properties of each powder are summarized in Table 4. Although the refractive indexes of the powders of Samples No. 4-4 to No. 4-10 were not measured, they can be assumed to be approximately the same as the refractive indexes of the powders of Samples No. 4-1 to No. 4-3.

[0120] [Table 4]

[0121] As can be seen from Table 4, powders No. 4-2, No. 4-3, No. 4-5 to No. 4-8, and No. 4-10, which correspond to examples of the second aspect of the present invention, are powders consisting of titanium phosphate-derived plate-like particles composed of either a titanium phosphate-derived compound in which the hydrogen of titanium phosphate is replaced with an alkali metal, or a titanium phosphate-derived compound in which an alkali metal is contained within the titanium phosphate crystal, and these powders had a ratio (actual specific surface area / presumed specific surface area) of 1.5 or more.

[0122] In contrast, the powders of samples No. 4-1, No. 4-4, and No. 4-9, which correspond to comparative examples of the second aspect of the present invention, were not powders composed of any of the titanium phosphate-derived plate-like particles described above, but powders composed of titanium phosphate plate-like particles, and the ratio (actual specific surface area / presumed specific surface area) of these powders was less than 1.5. In other words, the powders of Samples No. 4-2, No. 4-3, No. 4-5 to No. 4-8, and No. 4-10 have a ratio (actual specific surface area / presumed specific surface area) of 1.5 or more, and therefore have more surface irregularities and internal holes in the particles that make up the powder than the powders of Samples No. 4-1, No. 4-4, and No. 4-9, which have a ratio of less than 1.5. As a result, when used as a powder for cosmetics, a more refreshing feeling can be obtained.

[0123] In addition, the powders of Sample No. 4-2 and No. 4-3 did not differ significantly from the powder of Sample No. 4-1 in terms of whiteness, average thickness, average primary particle size, aspect ratio, refractive index, assumed specific surface area, and MIU, and thus had values ​​suitable for use as a powder for cosmetics. Similarly, the powders of Sample No. 4-5 to No. 4-8 did not differ significantly from the powder of Sample No. 4-4 in terms of whiteness, average thickness, average primary particle size, aspect ratio, assumed specific surface area, and MIU, and thus had values ​​suitable for use as a powder for cosmetics. Similarly, the powder of Sample No. 4-10 did not differ significantly from the powder of Sample No. 4-9 in terms of whiteness, average thickness, average primary particle size, aspect ratio, and assumed specific surface area, and thus had values ​​suitable for use as a powder for cosmetics.

[0124] In addition, while the powders of samples No. 4-1, No. 4-4, and No. 4-9 are acidic, the powders of samples No. 4-2, No. 4-3, No. 4-5 to No. 4-8, and No. 4-10 are neutral, and it was found that they have favorable properties (skin-friendly properties) as powders for cosmetics.

[0125] {Fifth embodiment: Third embodiment} <Sample No.5-1> Powder of sample No. 5-1 was prepared in the same manner as sample No. 4-1. The analysis results of the obtained powder using an X-ray diffractometer, the observation results using a scanning electron microscope, and each physical property were the same as those of the powder of sample No. 4-1. In addition, the friction coefficients, MIU (average friction coefficient) and MMD (average deviation of friction coefficient: average value of deviation of friction coefficient from average friction coefficient), were measured using the friction sensation tester "KES-SE" by Kato Tech Co., Ltd. During the measurement, double-sided tape was attached to the glass plate of the measurement table, and powder was placed on top of it and fixed in place. A 10 mm square silicon sensor was placed on this powder and moved under conditions of a static load of 25 g and a scanning speed of 1 mm / sec, and MIU and MMD were measured within a range of 20 mm. As a result, MIU was 0.98 and MMD was 0.010. Therefore, the ratio (MMD / MIU) was 0.009.

[0126] <Sample No.5-2> Powder of sample No. 5-2 was prepared in the same manner as sample No. 4-2. The analysis results of the obtained powder using an X-ray diffractometer, the observation results using a scanning electron microscope, and each physical property were the same as those of the powder of sample No. 4-2. The physical properties were as shown in Table 5. As shown in Table 5, the ratio (MMD / MIU) was 0.013.

[0127] <Sample No.5-3> Powder of sample No. 5-3 was prepared in the same manner as sample No. 4-3. The analysis results of the obtained powder using an X-ray diffractometer, the observation results using a scanning electron microscope, and each physical property were the same as those of the powder of sample No. 4-3. The physical properties were as shown in Table 5. As shown in Table 5, the ratio (MMD / MIU) was 0.016.

[0128] <Sample No.5-4> Powder of sample No. 5-4 was prepared in the same manner as sample No. 4-4. The analysis results of the obtained powder using an X-ray diffractometer, the observation results using a scanning electron microscope, and each physical property were the same as those of the powder of sample No. 4-4. The physical properties were as shown in Table 5. As shown in Table 5, the ratio (MMD / MIU) was 0.008.

[0129] <Sample No.5-5> Powder of sample No. 5-5 was prepared in the same manner as sample No. 4-6. The analysis results of the obtained powder using an X-ray diffraction device, the observation results using a scanning electron microscope, and each physical property were the same as those of the powder of sample No. 4-6. The physical properties were as shown in Table 5. As shown in Table 5, the ratio (MMD / MIU) was 0.013.

[0130] <Sample No.5-6> Powders of Samples No. 5-6 were prepared in the same manner as Samples No. 4-7. The results of analysis of the obtained powders using an X-ray diffractometer, the results of observation using a scanning electron microscope, and the physical properties were the same as those of Samples No. 4-7. The physical properties were as shown in Table 5. As shown in Table 5, the ratio (MMD / MIU) was 0.011. The physical properties of each powder are summarized in Table 5. Although the refractive indexes of the powders of Samples No. 5-4 to No. 5-6 were not measured, they can be assumed to be approximately the same as the refractive indexes of the powders of Samples No. 1 to 3.

[0131] [Table 5]

[0132] As can be seen from Table 5, the powders of Samples No. 5-2, No. 5-3, No. 5-5, and No. 5-6, which correspond to examples of the third aspect of the present invention, are powders consisting of titanium phosphate-derived plate-like particles composed of either a titanium phosphate-derived compound in which the hydrogen of titanium phosphate is replaced with an alkali metal, or a titanium phosphate-derived compound in which an alkali metal is contained within the titanium phosphate crystal, and these powders had a ratio (actual specific surface area / presumed specific surface area) of 1.5 or more.

[0133] In contrast, the powders of samples No. 5-1 and No. 5-4, which correspond to comparative examples of the third aspect of the present invention, are not powders composed of any of the titanium phosphate-derived plate-like particles described above, but are powders composed of titanium phosphate plate-like particles, and the ratio (actual specific surface area / presumed specific surface area) of these powders was less than 1.5. In other words, the powders of Samples No. 5-2, No. 5-3, No. 5-5, and No. 5-6 have a ratio (actual specific surface area / presumed specific surface area) of 1.5 or more, and therefore have more surface irregularities and internal holes in the particles that make up the powder than the powders of Samples No. 5-1 and No. 5-4, which have a ratio of less than 1.5. As a result, the MMD is higher, and when used as a powder for cosmetics, a more refreshing feeling is obtained.

[0134] The whiteness, average thickness, average primary particle size, aspect ratio, refractive index, assumed specific surface area, and MIU of the powders of samples No. 5-2 and No. 5-3 were not significantly different from those of sample No. 5-1, and were suitable for use as powders in cosmetics.Similarly, the whiteness, average thickness, average primary particle size, aspect ratio, assumed specific surface area, and MIU of the powders of samples No. 5-5 and No. 5-6 were not significantly different from those of sample No. 5-4, and were suitable for use as powders in cosmetics.

[0135] In addition, while the powders of samples No. 5-1 and No. 5-4 are acidic, the powders of samples No. 5-2, No. 5-3, No. 5-5, and No. 5-6 are neutral, and it was found that they have favorable properties (skin-friendly properties) as powders for cosmetics. In addition, the powders of samples No. 5-2 and No. 5-3 had the same MIU as the powder of sample No. 5-1, so they maintained their slipperiness, but had a large MMD, which made them rough. The friction coefficient ratio (MMD / MIU) of the powders of samples No. 5-2 and No. 5-3 was 0.011 or more. Therefore, when used as a powder for cosmetics, it not only has good slipperiness, but also provides a refreshing feeling.

[0136] In addition, the powders of samples No. 5-5 and No. 5-6 had the same MIU as the powder of sample No. 5-4, so they maintained slipperiness, but had a large MMD, which made them rough. The friction coefficient ratio (MMD / MIU) of the powders of samples No. 5-5 and No. 5-6 was 0.011 or more. Therefore, when used as a powder for cosmetics, it not only has good slipperiness, but also provides a refreshing feeling.

Claims

1. A method for increasing the specific surface area of ​​titanium phosphate plate-like particles, comprising: a first step of obtaining a liquid in which a powder of titanium phosphate plate-like particles is dispersed in an alkaline aqueous solution, the liquid having a pH of 5 or more and 9 or less; a second step of separating the titanium phosphate plate-like particles from the liquid; and a third step of drying the separated titanium phosphate plate-like particles.

2. The average thickness of the titanium phosphate plate-like particles is 0.01 μm or more and 4 μm or less, 2. The method for increasing the specific surface area of ​​titanium phosphate plate-like particles according to claim 1, wherein the aspect ratio, which is a value obtained by dividing the average primary particle diameter of the titanium phosphate plate-like particles by the average thickness, is 5 or more.

3. 3. The method for increasing the specific surface area of ​​titanium phosphate plate-like particles according to claim 2, wherein the average primary particle size is from 0.05 μm to 20 μm.

4. The method for increasing the specific surface area of ​​titanium phosphate plate-like particles according to any one of claims 1 to 3, wherein the titanium phosphate plate-like particles are hexagonal plate-like particles.

5. A powder comprising titanium phosphate-derived plate-like particles, which are either a titanium phosphate-derived compound in which hydrogen in titanium phosphate is replaced with an alkali metal, or a titanium phosphate-derived compound in which an alkali metal is contained within the titanium phosphate crystal, A powder having a mean coefficient of friction (MIU) of 1.45 or less, and a ratio (MMD / MIU) of the mean coefficient of friction (MMD) to the mean coefficient of friction (MIU) of 0.011 or more.

6. The average thickness of the titanium phosphate-derived plate-like particles is 0.01 μm or more and 4 μm or less, 6. The powder according to claim 5, wherein the aspect ratio, which is a value obtained by dividing the average primary particle size of the titanium phosphate-derived plate-like particles by the average thickness, is 5 or more.

7. 7. The powder according to claim 6, wherein the average primary particle size is 0.05 μm or more and 20 μm or less.

8. The powder according to claim 5, wherein the titanium phosphate-derived plate-like particles are hexagonal plate-like particles.

Citation Information

Patent Citations

  • AU5724969A

  • Porous sheet lithium ion battery LiTi2(PO4)3 electrode material and preparation method thereof

    CN104477870A

  • Method for preparing shuttle-shaped single-layer sheet-like NaTi2 (PO4) 3 electrode material

    CN105271158A

  • Preparation of titanium phosphate crystals

    GB1282594A

  • JP1974001720A